The Effects of Performance Measurement and Compensation on Motivation - Marco van Herpen; C. Mirjam van Praag; Kees Cools (Tinbergen Institute, 2003)
This paper analyzes empirically the relationship between pay and performance. Economic and psychological theories predict that the design and implementation of a performance measurement and compensation system affect the motivation of employees. Our survey results demonstrate a positive relationship between the perceived characteristics of the complete compensation system and extrinsic motivation. Intrinsic motivation is not affected by the design of monetary compensation, but by promotion opportunities. The compensation system also significantly affects work satisfaction and turnover intent. Our results have both managerial as well as policy implications.
Keywords: J41; J33; 330; Performance measurement; Compensation; Promotions; Intrinsic Motivation; Extrinsic Motivation.; Leistungsentgelt; Leistungsanreiz; Leistungsmotivation; Betriebliche Kennzahl